Material for synergistically producing water and electricity based on interface evaporation as well as preparation method and application of material
Through the Janus structured nickel/nickel selenide material prepared by laser processing and solvent thermal method in water evaporation power generation devices, combined with the temperature difference power generation module, the problem of low performance of existing water evaporation power generation devices is solved, and efficient seawater desalination and temperature difference power generation are achieved.
Patent Information
- Application Number
- CN202411789222.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing water evaporation power generation devices have problems such as complex device assembly process, poor power generation performance, low evaporation efficiency, expensive materials and complex preparation processes, which are difficult to meet practical applications.
A collaborative aquatic electrical material based on interfacial evaporation was used to process the foam nickel foam substrate by laser processing, and the nickel foam/nickel selenide (NiSe/NF) was synthesized with solvothermal method, and the upper layer was sprayed with cetyl trimethoxysilane to prepare Janus structural materials with different wettability on the upper and lower surfaces. The material is combined with a temperature differential power generation module to generate electricity simultaneously while seawater desalination.
Efficient seawater desalination and temperature differential power generation are achieved, with an evaporation rate of 2.22kg·m-2·h-1 and a production voltage of 95.7mV, which is equivalent to 5.98V m-2, which significantly improves the efficiency and performance of water evaporation power generation.
Smart Images

Figure CN119612656A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of seawater desalination, and in particular to a material for synergistic water and electricity production based on interface evaporation, and a preparation method and application thereof. Background Art
[0002] As the population continues to grow, energy shortages are crucial to the sustainable survival and development of mankind. The global energy system is also undergoing a transition from almost complete reliance on fossil energy to more reliance on clean and renewable energy.
[0003] Interfacial solar water evaporation has the characteristics of high photothermal conversion rate, fast water evaporation rate, low cost, simple operation and environmental friendliness. In the field of solar energy utilization, in addition to water evaporation to achieve seawater desalination, it is also possible to use temperature difference power generation to directly convert thermal energy into electrical energy without the need for intermediate conversion of mechanical energy. Therefore, the development prospects of water and power cogeneration technology are broad, and it is an extremely important research field in addressing the problem of global energy shortage. Interfacial solar water evaporation technology mainly relies on the development of photothermal conversion materials. The Janus structure is a unique structure of photothermal conversion composite materials, with different properties on both sides. This opposite property specifically refers to two types, one is that the two sides of the membrane have opposite charges, and the other is that the wettability of the two sides of the membrane is different. Among them, the asymmetric wettability structure in the interfacial solar water evaporation allows seawater to be transported unidirectionally from the bottom to the surface, water evaporation occurs at the hydrophobic interface, and pollutants are blocked under the hydrophilic layer, so that the sample has a certain anti-fouling ability. Designing the interfacial solar evaporator into a Janus structure can obtain excellent salt resistance and anti-fouling performance without reducing the evaporation rate, which is a major breakthrough in the field of seawater desalination. The technology related to the present invention is a Janus structure photothermal conversion material with different wettability on both sides of the film.
[0004] Chinese patent publication number CN 113603935 A proposes a composite aerogel with Janus characteristics. The upper layer of the composite aerogel is silane-modified cellulose nanofibril / Ti3C2Tx MXene aerogel, and the lower layer is cellulose nanofibril aerogel. The upper layer is hydrophobic and the lower layer is hydrophilic. It can not only desalinate seawater but also has certain anti-fouling properties. Although the patent achieves the synergy of evaporation and salt resistance through the Janus structure, the power generation performance of the evaporator has not been further studied. Among the many green energy power generation methods, water evaporation power generation is a power generation method that converts the heat energy of the surrounding environment into electrical energy through water evaporation. This method can generate electricity using natural phenomena without the need for external mechanical action and energy input. The water evaporation power generation devices reported so far have problems such as complex device assembly process, poor power generation performance, low evaporation efficiency, expensive materials and complex preparation process, which are difficult to meet practical applications. Selecting photothermal materials with high photothermal conversion capabilities to construct anti-fouling and anti-salt Janus structure solar evaporators, while producing water and electricity has become an urgent need in today's energy shortage situation. Summary of the invention
[0005] In order to achieve efficient seawater desalination and simultaneously obtain electrical energy through temperature difference power generation, the present invention provides a material based on interfacial evaporation to synergistically produce water and electricity. The material is a Janus structure with a hydrophobic upper layer and a hydrophilic lower layer. The Janus structure is not only conducive to the unidirectional transport of seawater from bottom to top, but also can prevent salt from accumulating on the upper surface and clogging the pore structure.
[0006] The invention also provides a preparation method and application of the material.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A material based on interfacial evaporation to synergistically produce water and electricity, characterized in that it uses laser-processed nickel foam as a substrate and selenium powder as a main raw material. Ethylene glycol and ethylenediamine are used as main solvents to synthesize nickel foam / nickel selenide (NiSe / NF for short) by a solvothermal method, and then hexadecyltrimethoxysilane is sprayed on the upper layer. After vacuum drying, a material with a Janus structure with different wettability on the upper and lower surfaces is obtained. This material is combined with a temperature difference power generation module to produce water and electricity simultaneously.
[0009] Furthermore, the ethylene glycol and ethylenediamine are chemically pure, and are mixed in equal volume proportions and diluted with water to form a mixed solution of ethylene glycol and ethylenediamine, wherein the ethylene glycol and ethylenediamine together account for (50-60)% of the volume of the mixed solution, preferably 57.1%.
[0010] Furthermore, the amount of selenium powder added is 5-6 g, preferably 5.71 g, per 1 liter of the mixed solution of ethylene glycol and ethylenediamine.
[0011] The method for preparing the Janus nickel foam / nickel selenide of the present invention comprises the following steps:
[0012] Step 1: Laser processing nickel foam substrate
[0013] The cleaned nickel foam substrate is laser processed to change the upper and lower surfaces of the nickel foam from super-hydrophobic to hydrophilic, thereby increasing the surface roughness and facilitating the subsequent construction of a composite material using a solvothermal method.
[0014] Step 2: Preparation of nickel foam / nickel selenide (NiSe / NF) synthesis method
[0015] Ethylene glycol and ethylenediamine are mixed in a sealed container in proportion and diluted with water to a required concentration, and then selenium powder and laser-treated nickel foam are added and reacted under heating conditions to obtain nickel foam / nickel selenide NiSe / NF.
[0016] Step 3: Preparation of Janus nickel foam / nickel selenide
[0017] A certain amount of hexadecyltrimethoxysilane was sprayed on the surface of the prepared nickel foam / nickel selenide NiSe / NF, and vacuum dried to obtain Janus nickel foam / nickel selenide.
[0018] Furthermore, in step 2, the heating condition refers to keeping the temperature at (150-170)°C for 4-6 hours.
[0019] The Janus nickel foam / nickel selenide of the present invention is mainly used in seawater desalination and evaporation power generation. The method of using the Janus nickel foam / nickel selenide in the seawater desalination process is as follows: the Janus nickel foam / nickel selenide is used as an absorber and combined with polyethylene foam and cotton wool to form a photothermal evaporator, wherein the polyethylene foam is used as an insulator to reduce heat conduction loss during evaporation, and the cotton wool is used as a transmission channel for seawater, and then the photothermal evaporator is placed in a container containing seawater.
[0020] The method of use in the process of water and electricity generation is: the Janus nickel foam / nickel selenide is used as an absorber and combined with polyethylene foam and absorbent paper to form a photothermal evaporator, and then the thermoelectric power generation module is installed between the polyethylene foam and the absorbent paper of the photothermal evaporator to construct a water and electricity generation device. The polyethylene foam is used to reduce heat loss during the evaporation process, and the absorbent paper is used as a channel for seawater transmission. Then the water and electricity generation device is placed in a container containing seawater, and the thermoelectric power generation module is connected to the electrochemical workstation.
[0021] The advantages of the present invention are:
[0022] 1. The raw material nickel foam has the advantages of stable physical and chemical properties, good processing performance and high thermal conductivity. Laser processing of nickel foam improves its wettability, and the surface changes from superhydrophobic to hydrophilic, increasing the surface roughness, which is more conducive to the solvent thermal synthesis of NiSe on the nickel foam skeleton. At the same time, nickel selenide has good light absorption and photothermal conversion properties. These characteristics are conducive to the sample for efficient seawater desalination and temperature difference power generation.
[0023] 2. The upper and lower surfaces of the Janus nickel foam / nickel selenide of the present invention have completely different physical and chemical properties. The upper surface is sprayed with hexadecyltrimethoxysilane, which can not only be modified to become hydrophobic, but also firmly block the seawater in the hydrophilic layer of the nickel foam / nickel selenide below during the photothermal seawater desalination process, preventing the accumulation of salt on the upper surface and the erosion of the light-absorbing layer, thereby ensuring the operating stability of the evaporator and the complex salt cleaning problem.
[0024] 3. The Janus nickel foam / nickel selenide can not only desalinate seawater through interface evaporation, but also, in a wet state, by combining the sample with the TE module, the sample receives the heat from the sun and transfers it to the upper surface of the TE module, so that a temperature difference is generated between the upper and lower surfaces of the module for thermoelectric power generation. According to the test, when the size of the selected TE module is (4*4) cm, the size of the Janus nickel foam / nickel selenide is also (4*4) cm. In this way, under the irradiation of a strong sunlight (1kw m -2 ), while producing water, this thermoelectric generator can synchronously obtain a voltage of 95.7mV, equivalent to 5.98V m -2 .
[0025] 4. The water evaporation rate of the Janus nickel foam / nickel selenide under one sun reached 2.22 kg·m -2 ·h -1 , which is higher than most of the composite materials for synergistic water and electricity production in current research work. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a simplified diagram of the Janus nickel foam / nickel selenide of Embodiments 1 to 4 of the present invention.
[0027] Figure 2 Figures 2(a) and 2(b) are SEM images of the nickel foam / nickel selenide sample NiSe / NF sample prepared by using ethylene glycol and ethylenediamine with different volume concentrations in the present invention, wherein 2(a) and 2(b) are SEM images of the sample prepared when the volume concentration of ethylene glycol and ethylenediamine is 100%, and 2(c)-2(d) are SEM images of the sample prepared when the volume concentration of ethylene glycol and ethylenediamine is 57.1%.
[0028] Figure 3This is a test diagram of the evaporation performance of Junas nickel foam / nickel selenide according to Examples 1 to 4 of the present invention.
[0029] Figure 4 This is a one-hour surface temperature curve of the Janus nickel foam / nickel selenide of Examples 1 to 4 of the present invention.
[0030] Figure 5 This is a contact angle diagram of the upper and lower surfaces of Janus nickel foam / nickel selenide according to Example 1 of the present invention.
[0031] Figure 6 This is a 20-hour cycle test chart of the Janus nickel foam / nickel selenide of Example 1 of the present invention for desalinating seawater under a certain light intensity.
[0032] Figure 7 This is a diagram of the Janus nickel foam / nickel selenide water and electricity production device according to the first embodiment of the present invention.
[0033] Figure 8 The voltage curve of the Janus nickel foam / nickel selenide in Example 1 of the present invention generated in one hour under different light intensities when producing electricity in a wet state.
[0034] Fig. 9 The mass loss of the nickel foam / nickel selenide sample obtained by the solvothermal method by changing the volume concentration of ethylene glycol and ethylenediamine in the present invention within one hour. DETAILED DESCRIPTION
[0035] The following is based on the attached Figure 1-9 The technical solution of the present invention is further explained in conjunction with specific embodiments.
[0036] Embodiment 1
[0037] participate Figure 1 The steps of preparing Janus nickel foam / nickel selenide according to the present invention are as follows:
[0038] Step 1: Preparation of laser processed nickel foam
[0039] The nickel foam was cut into thin sheets of 2cm*2cm in size and placed in a beaker. Then, it was ultrasonically cleaned with 3M dilute hydrochloric acid solution for 30min, cleaned with deionized water for 10min, rinsed with anhydrous ethanol for 10min, and cleaned with deionized water for 10min. Finally, the cleaned foam metal was placed in a vacuum drying oven and dried at 30-50℃ for 6h to obtain a clean foam metal. Then, laser processing was performed by setting certain parameters such as laser processing power of 7w and laser processing speed of 100mm / s to "change the wettability of the surface of the nickel foam substrate."
[0040] Step 2: Preparation of NiSe / NF foam samples
[0041] Take 10 ml of chemically pure ethylene glycol solution and 10 ml of ethylenediamine solution respectively, stir magnetically for 30 minutes under closed conditions at room temperature, then add deionized water to 35 ml and continue stirring for 15-20 minutes, then add 0.2 g of Se powder and continue stirring for 30 minutes, and after stirring, the desired precursor solution is obtained. Quickly transfer the precursor solution and the cleaned and laser-processed nickel foam to the core of the reactor, then place the prepared reactor in an oven and keep it warm at about 160°C for 4-6 hours; after the reaction is completed, wait for the reactor to cool completely, and then take out the prepared composite material with tweezers, wash it with deionized water several times, and dry it in a drying oven at 40°C for 6 hours to obtain nickel foam / nickel selenide.
[0042] Step 3: Preparation of Janus nickel foam / nickel selenide
[0043] The prepared nickel foam / nickel selenide was dried and taken out, and 1 ml of hexadecyltrimethoxysilane was measured and sprayed on the surface of the nickel foam / nickel selenide with a spray gun. After vacuum drying at 35° C. overnight, Janus nickel foam / nickel selenide was obtained.
[0044] Step 4: Application
[0045] Application 1: The Janus nickel foam / nickel selenide is used as an absorber and combined with polyethylene foam and cotton wool to make a photothermal evaporator sample, wherein the polyethylene foam is used as an insulator to reduce heat conduction loss during evaporation, and the cotton wool is used as a transmission channel for seawater. The photothermal evaporator sample is then placed in a polytetrafluoroethylene container filled with seawater, and the polytetrafluoroethylene reactor core container is placed on a balance and irradiated with a simulated light source. The mass changes at different times are recorded, the evaporation rate of seawater is calculated, and the photothermal conversion efficiency is then obtained.
[0046] Application 2: The Janus nickel foam / nickel selenide is used as an absorber and combined with a thermoelectric power generation module, polyethylene foam, and absorbent paper to construct Figure 7 The water and electricity generation device samples shown are from Figure 7 It can be seen that the water-generating and electricity-generating device is composed of a Janus nickel foam / nickel selenide absorber, absorbent paper, a thermoelectric power generation module and polyethylene foam from top to bottom, wherein the polyethylene foam is used to reduce heat loss during evaporation, and the absorbent paper is used as a channel for seawater transmission. The sample of the water-generating and electricity-generating device is then placed in a large beaker filled with seawater, and the thermoelectric power generation module is connected to the electrochemical workstation and irradiated with a simulated light source to record the voltage values generated at different times.
[0047] In order to adapt to the size of the temperature difference power generation module, the absorber in the water-generating and power-generating device sample constructed in the laboratory is composed of four samples prepared in Example 1, which are assembled into a size of 4 cm*4 cm. After testing, the single water evaporation rate of the Janus nickel foam / nickel selenide under one light intensity is 2.22 kg·m -2 ·h -1 The unit voltage of the water-electricity device under one light intensity is 95.7mV when the water evaporates in the wet state. This is equivalent to the unit voltage of 5.98V m per square meter of absorber under one light intensity when the water evaporates in the wet state. -2 .
[0048] from Figure 2 (c) and 2(d) are SEM images of nickel foam / nickel selenide of the present invention. It can be seen that the nickel selenide with a flaky structure synthesized on the surface of the nickel foam skeleton increases the scattering path of light when sunlight irradiates the surface, thereby improving the utilization rate of sunlight, making the nickel foam / nickel selenide have high light absorption and high photothermal conversion performance.
[0049] Embodiment 2
[0050] Except that the third step of spraying 1 ml of hexadecyltrimethoxysilane solution on the surface of the nickel foam / nickel selenide with a spray gun was changed to no spraying, the rest of the preparation process and parameters were the same as those in Example 1. The mass loss of the prepared nickel foam / nickel selenide under one sun intensity was 1.65 kg·m -2 ·h -1 ,like Figure 3 shown.
[0051] Embodiment 3
[0052] Except that the third step of spraying 1 ml of hexadecyltrimethoxysilane solution on the surface of the nickel foam / nickel selenide with a spray gun was changed to spraying 0.5 ml, the other processes and parameters were the same as those in Example 1. The mass loss of the prepared Janus nickel foam / nickel selenide under one sun intensity was 1.73 kg·m -2 ·h -1 ,like Figure 3 shown.
[0053] Embodiment 4
[0054] Except that the third step of spraying 1 ml of hexadecyltrimethoxysilane solution on the surface of the nickel foam / nickel selenide with a spray gun was changed to spraying 1.5 ml, the other processes and parameters were the same as those in Example 1. The mass loss of the prepared Janus nickel foam / nickel selenide under one sun intensity was 1.87 kg·m -2 ·h -1 ,like Figure 3 shown.
[0055] Compare Figure 3 It can be seen from the evaporation rates of Examples 1 to 4 that spraying different volumes of hexadecyltrimethoxysilane solution on the surface of nickel foam / nickel selenide has a certain effect on the evaporation rate of the prepared Janus nickel foam / nickel selenide. Spraying too much will block the pores and hinder the upward transportation of seawater. Spraying too little will cause poor surface hydrophobicity of Janus nickel foam / nickel selenide. Therefore, the present invention preferably sprays 1 ml of hexadecyltrimethoxysilane solution on the surface of 2cm*2cm nickel foam / nickel selenide. In addition, since the basic requirement for temperature difference power generation performance is excellent light-to-heat conversion performance, the power generation test in wet state is only carried out in Example 1 with the highest water evaporation rate.
[0056] from Figure 3 From the mass loss curves of the four embodiments of the present invention sprayed with different volumes of hexadecyltrimethoxysilane solution on the Janus nickel foam / nickel selenide under one sunlight intensity, it can be seen that the evaporation rate of seawater is greatly increased by using the photothermal material as an absorber. After spraying the hydrophobic substance hexadecyltrimethoxysilane solution, the evaporation rate of seawater is also significantly improved, and the Janus nickel foam / nickel selenide sprayed with 1ml of hexadecyltrimethoxysilane solution has the best performance. This also shows that the volume of hexadecyltrimethoxysilane solution sprayed during the surface modification of nickel foam / nickel selenide has an effect on the photothermal performance of the absorber.
[0057] from Figure 4 It can be seen that the temperature curves of the four embodiments of the Janus nickel foam / nickel selenide of the present invention under one light intensity irradiation show that the surface temperature of the Janus nickel foam / nickel selenide sprayed with hexadecyltrimethoxysilane is higher than that of the original nickel foam and nickel foam / nickel selenide, indicating that the sample surface has excellent photothermal conversion ability.
[0058] from Figure 5 The contact angle diagram of the upper and lower surfaces of the Janus nickel foam / nickel selenide of the present invention shows that the upper surface of the material is hydrophobic and the lower surface is hydrophilic.
[0059] Figure 6 It can be seen from the cyclic test curve of the Janus nickel foam / nickel selenide of the present invention that it can maintain a stable high evaporation rate under continuous sunlight and there is almost no salt precipitation on the sample surface before and after the cycle, indicating that in the process of seawater desalination, Janus nickel foam / nickel selenide has excellent cyclic stability and salt resistance.
[0060] from Figure 8 It can be seen that the one-hour voltage change curve of the Janus nickel foam / nickel selenide in the wet state under different light intensities can be seen. As can be seen from the figure, the higher the light intensity is in the same time, the higher the voltage is.
[0061] It should be noted that in the preparation of the nickel foam / nickel selenide sample NiSe / NF, the volume concentration of the ethylene glycol and ethylenediamine mixed solution needs to be strictly controlled to ensure that the obtained NiSe / NF has good photothermal efficiency. In order to verify this, two groups of experiments were conducted. Among them:
[0062] One group is to change the volume concentration of ethylene glycol and ethylenediamine in the mixed solution of Example 1 under the same conditions, and keep other parameters unchanged, so as to obtain nickel foam / nickel selenide samples NiSe / NF with different volume concentrations. The mass loss of nickel foam / nickel selenide samples NiSe / NF prepared by ethylene glycol and ethylenediamine with different volume concentrations after one hour of light exposure is analyzed, and the analysis results are shown in Fig. 9 ,from Fig. 9 It can be seen that the volume concentration ratio of the mixed solution of ethylene glycol and ethylenediamine has a great influence on the evaporation rate of the nickel foam / nickel selenide NiSe / NF sample. Reducing the volume concentration of ethylene glycol and ethylenediamine in the mixed solution can significantly increase the evaporation rate of the nickel foam / nickel selenide sample NiSe / NF, but the lower the better is not necessarily the case. This shows that the volume concentration ratio of the mixed solution of ethylene glycol and ethylenediamine is not good when it is too high or too low. However, when the volume concentration of ethylene glycol and ethylenediamine in the mixed solution is 57.1%, the evaporation rate of the nickel foam / nickel selenide sample NiSe / NF is significantly improved. Taking all factors into consideration, the present invention ultimately controls the volume concentration of ethylene glycol and ethylenediamine in the mixed solution to be (50-60)%.
[0063] Another group prepared nickel foam / nickel selenide sample NiSe / NF according to the experimental parameters of Example 1 while controlling the volume concentration of the ethylene glycol and ethylenediamine mixed solution to 100%. The SEM image of the obtained sample is shown in FIG. Figure 2 (a) and 2(b), from Figure 2 As can be seen from the phase images of (a) and 2(b), the surface of the nickel foam / nickel selenide sample NiSe / NF material prepared when the volume concentration of the ethylene glycol and ethylenediamine mixture is 100% is smooth, while in contrast, the surface of the NiSe / NF material prepared in Example 1 of the present invention (see Figure 2 (c)-2(d)) The surface is rougher. The rough surface structure can increase light scattering and improve the utilization rate of sunlight, thereby enabling better solar thermal desalination and temperature difference power generation.
[0064] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.
Claims
1. A material based on interfacial evaporation to produce water and electricity, characterized in that: It uses laser-processed nickel foam as the substrate and selenium powder as the main raw material. Ethylene glycol and ethylenediamine are used as the main solvents, and the solvent concentration and the amount of raw material added are controlled. The nickel foam / nickel selenide is synthesized by the solvent thermal method, and then hexadecyltrimethoxysilane is sprayed on the upper layer. After vacuum drying, a material with a Janus structure with different wettability on the upper and lower surfaces is obtained. This material is combined with a temperature difference power generation module to produce water and electricity simultaneously.
2. The material based on interfacial evaporation to produce water and electricity according to claim 1, characterized in that: The ethylene glycol and ethylenediamine are chemically pure. Equal volumes of the two are taken and diluted with water to form a mixed solution of ethylene glycol and ethylenediamine, wherein the ethylene glycol and ethylenediamine together account for (50-60)% of the mixed solution.
3. The material based on interfacial evaporation to produce water and electricity according to claim 2, characterized in that: The ethylene glycol and ethylenediamine together account for 57.1% of the volume of the mixed solution.
4. The material based on interfacial evaporation to produce water and electricity according to claim 2, characterized in that: The amount of selenium powder added is 5-6 g of selenium powder per 1 liter of the mixed solution of ethylene glycol and ethylenediamine.
5. The material based on interfacial evaporation to produce water and electricity according to claim 4, characterized in that: The amount of selenium powder added is 5.71 grams of selenium powder per 1 liter of the mixed solution of ethylene glycol and ethylenediamine.
6. A method for preparing a material based on interfacial evaporation for synergistic water and electricity production as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Laser processing nickel foam substrate The cleaned nickel foam substrate is laser processed to change the upper and lower surfaces of the nickel foam from super-hydrophobic to hydrophilic, thereby increasing the surface roughness, which is beneficial for the subsequent construction of nickel foam / nickel selenide materials using a solvothermal method; Step 2: Preparation of nickel foam / nickel selenide synthesis method Ethylene glycol and ethylenediamine are mixed in a sealed container according to a certain proportion and diluted with water to a required concentration, and then selenium powder and laser-treated nickel foam are added to react under heating conditions to obtain nickel foam / nickel selenide; Step 3: Preparation of Janus nickel foam / nickel selenide A layer of hexadecyltrimethoxysilane is sprayed on the surface of the prepared nickel foam / nickel selenide, and vacuum drying is performed to obtain Janus nickel foam / nickel selenide.
7. The method for preparing a material for synergistic water and electricity production based on interfacial evaporation according to claim 6, characterized in that: In step 2, the heating condition refers to keeping the temperature at 150-170° C. for 4-6 hours.
8. An application method of the material based on interfacial evaporation to produce water and electricity as claimed in claim 1, characterized in that: Janus nickel foam / nickel selenide is used as an absorber and combined with polyethylene foam and absorbent paper to make a photothermal evaporator. The temperature difference power generation module is then installed between the polyethylene foam and absorbent paper of the photothermal evaporator to construct a water and electricity production device.
9. An application method of the material based on interfacial evaporation to produce water and electricity as claimed in claim 1, characterized in that: Janus nickel foam / nickel selenide was used as an absorber combined with polyethylene foam and absorbent paper to make a photothermal evaporator.
Citation Information
Patent Citations
Composite aerogel with Janus characteristic as well as preparation method and application thereof
CN113603935A
Nano-composite optothermal response system, resin material and smart glass
CN105713238A
Preparation method and application of foamed nickel-based Ni3Se2 nano material
CN106024395A
Janus double-layer aerogel as well as preparation method and application thereof
CN115725112A
Preparation method of ceramic-based double-sided evaporation desalination and driving power generation device based on sandwich structure
CN116201706A
Cited By
Vertical heterogeneous water-salt co-production solar evaporator and preparation method and application thereof
CN121717428A